Transições de fase induzidas por pressão e tamanho de partícula no ferroelástico Pb8O5(VO4)2 - Araújo, Bruno Sousa (2014)
Ferroelastic compounds are characterized by the possibility to present two or more states of spontaneous strain which could be permuted by application of mechanical stress. Pb8O5(VO4)2 can be classified as belonging to this group. Its crystal structure is not well defined in the literature due to certain adversities found during the data analysis. However, making use of X-ray diffraction in several crystals of this compound we will discuss their probable point groups. It is also known that there is a direct relation between the states of strain and the domains pattern at ambient conditions of temperature and pressure. Several spectroscopic techniques were employed in order to analyze how the crystal structure of these compounds varies according to the dimensions of each crystal. Therefore, we observed the existence of three phases under ambient conditions as well as the possibility of a spontaneous phase transition in crystals of order to units of square micrometers. The structural behavior of Pb8O5(VO4)2 with increasing temperature has been studied in detail by different authors. They reported the existence of two phase transitions on heating, one second-order transition at about 440 K and another first-order around 520 K. The first-order phase transition leads the Pb8O5(VO4)2 crystals of ferroelastic phase to paraelastic phase. However, since ferroelastics crystals show changes of state of spontaneous strain through the application of mechanical stress, we made use of Raman scattering measures with increasing of hydrostatic pressure on samples of Pb8O5(VO4)2 to accompany the spectral behavior of the same during these pressure variations. This way we observed a phenomenon of amorphization of the sample around 11 GPa and obtained strong evidences from three phase transitions at approximately 1, 3.5 and 6 GPa.